Strategies for developing the skillsof comunication in the area of english. Applicable in the ninth and tenth levels of basic education in the Manuel Cordova Galarza High School - Criollo, Miriam; Otorongo, Lucía
This thesis is designed for public high school English teachers. This includes an English didactic guide. In addition, this thesis is to address the students of the ninth and tenth levels of basic education in Manuel Cordova Galarza high school who wish to learn English through their favorite topics. In the introduction there is a short synthesis of the organization of this thesis. The source used was discussed evaluating and selecting material, TEFL for teenager´s workbooks, and reading texts from the internet. This thesis offers suggestions for developing the four skills of the language through a variety of activities. We have provide a selection of what we consider to be the most attractive and useful activities for an English didactic guide. Therefore, before we designed the English didactic guide we conducted an analysis of the main necessities and interests of the students who use these activities. We, as teachers, know that we work with human beings who have their own needs, interests, weaknesses, strengths, feelings, personality, problems, and learning experiences. Thus, we were challenged to search for additional methodological strategies. The authors of this thesis are pleased to contribute this work the English teaching and learning community